Transformationsverträge sind eine Sackgasse: In Erinnerung an Irene Barbers (1966–2025) - Mittermaier, Bernhard (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2025)
This article analyses the impact of transformative agreements on the development of the open access landscape. It is shown that, regardless of their potential economic benefits, these transformative agreements do not effectively advance the transformation of the publishing industry because they do not sufficiently promote the flipping of subscription journals into open access journals. The flipping rates of two major publishers (Springer Nature and Wiley) and the results of the cOAlition S ‘Transformative Journals’ programme are examined using various approaches, with the result that the transformation of the majority of journals to open access via transformative agreements would take many decades. As a consequence, the author calls for greater promotion of Diamond Open Access as an alternative to transformation agreements, as well as for critical evaluation of transformation agreements before their renewal.
Keywords: Open Access; Open Access transformation; Transformation agreement; Journal flipping; Journal transformation; Journal analysis